Konsep Penataan Ruang dan Pengelolaan Limbah yang Ramah Lingkungan pada Kawasan Industri - Ananda Malaieka Andjani; Muhammad Fathien Azmy; Yashinta Kumala Dewi Sutopo (Jurnal Wilayah & Kota Maritim (Journal of Regional and Maritime City Studies), 2017)
Spatial Planning plays an important role in making space efficient and providing the facilities and infrastructure needed in an industrial area. Thus, to achieve environmental friendly conditions pollution control can be done by means of environmentally friendly waste management. Important aspects in spatial planning include, location, environmental integration, zoning and land efficiency arrangements, provision of green space, provision of facilities and infrastructure, and environmentally friendly construction. Waste management includes aspects of component supply, conservation, reuse, attention to technology, and minimization of waste in the production process. This study aims to identify spatial planning, identify waste management, and arrange spatial direction directives and environmentally friendly waste management at PT. Kima The analysis used in this research is analysis of aspects including comparative analysis, descriptive analysis, and gap analysis. The results of this study show that there are still some environmentally friendly aspects that are not considered in the spatial planning of PT. KIMA like, does not apply zoning, RTH <10% and so on. In addition, waste management is also not optimal in reducing waste production activities. Therefore, the direction in spatial planning and waste management in PT. KIMA, among others, pays attention to environmentally friendly construction, waste utilization, enforcement of regulations so that the industry carries out waste reduction, and others.